Regulations on The Job Creation Law Regarding Job Loss Guarantees In The Context of Legal Protection for Workers - Alfathoni, Muhammad Ilham; Lubis, Cherilla Izzata Putri; Astapradja, Muhammad Bijak Ramadhan (Program Studi Magister Kenotariatan Fak. Hukum Univ. Andalas, 2023)
Job Loss Guarantee (JKP) is a program created by the government for workers who experienced termination of employment (PHK) with benefits in cash, job market information, and job training. Workers are still overshadowed by the uncertainty of legal protection, including JKP. JKP has been guaranteed by the Job Creation Law Act No. 11 of 2020 and then published government regulation (PP) number 37 of 2021 concerning implementing the Job Loss Guarantee program. However, the regulation of Article 20 PP No. 37 of 2021 concerning JKP explains the benefits of JKP for participants who experience layoffs are excluded from dismissals due to resignation, total permanent disability, retirement or death. This study outlines two problems: how to follow up the Job Creation Law to protect workers? and the rights of workers if they experience job loss through termination of employment?. The research method used is juridical normative. Implementing the Job Creation Law made by the government to bring a change to the JKP system is expected to be carried out in the interests of workers. Then, the government, as the controller, constantly supervises the implementation of the Job Creation Law and the National Social Security System in the field so that workers will get legal certainty.